DIMINISHING OF POWER LOSSES IN CONTACT LINES FOR ACCOUNT OF OPTIMIZATION OF DISTANCE BETWEEN BY TRAINS - Калашников, Константин Алексеевич (Eastern-European Journal of Enterprise Technologies, 2012)
It’s offered the method of diminishing of power losses in a contact lines due to optimization of distance between trains, the choice. The autors gave the mathematical method of optimization of distances between trains on the criterion of a minimum of losses of power in a contact lines.